2013
DOI: 10.3402/meo.v18i0.21194
|View full text |Cite
|
Sign up to set email alerts
|

Decline of medical student idealism in the first and second year of medical school: a survey of pre-clinical medical students at one institution

Abstract: BackgroundIdealism declines in medical students over the course of training, with some studies identifying the beginning of the decline in year 3 of US curricula. PurposesThis study tested the hypothesis that a decline in medical student idealism is detectable in the first two years of medical school.MethodsWe sought to identify differences in survey responses between first-year (MS1) and second-year (MS2) medical students at the beginning (T1) and end (T2) of academic year 2010 on three proxies for idealism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 29 publications
2
37
0
4
Order By: Relevance
“…This is of concern since a positive attitude toward psycho-social aspects of the medical profession has been associated with a greater degree of communication with patients as well as humanistic traits during the provision of care 27 . Our findings are not without precedent, however, as a decline in idealism during the medical course and internship periods has been previously identified 28 . This decline is particularly evident after the first couple years 29,30 when students are confronted with the massive amount of technology, patient volume, disease severity, financial constraints, and a lack of role models that would perhaps emphasize their continued focus on humanistic aspects of patient care 31 .…”
Section: Discussionsupporting
confidence: 56%
“…This is of concern since a positive attitude toward psycho-social aspects of the medical profession has been associated with a greater degree of communication with patients as well as humanistic traits during the provision of care 27 . Our findings are not without precedent, however, as a decline in idealism during the medical course and internship periods has been previously identified 28 . This decline is particularly evident after the first couple years 29,30 when students are confronted with the massive amount of technology, patient volume, disease severity, financial constraints, and a lack of role models that would perhaps emphasize their continued focus on humanistic aspects of patient care 31 .…”
Section: Discussionsupporting
confidence: 56%
“…As students enter medical college around the age of 17–18 years, the preclinical year is of prime importance as a time for their first exposure to a professional learning environment. While the student entering medical school may not yet possess full‐fledged professional values, studies have shown that it is these very students who are the most idealistic with regards to learning key medical skills and fulfilling obligations to their community, attitudes which wane with years of training (Baingana et al, ; Morley et al, ; Pagnin et al, ; Mader et al, ), and they are less self‐centered than their senior counterparts (Klemenc‐Ketis and Vrecko, ). The first year of medicine would be an ideal foundation to begin the integration of professionalism teaching into medical education in India.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that students tend to lose empathic and idealistic motivations over the course of medical education. This loss of idealism includes a decreased interest in working in underserved communities, feeling of less responsibility for the health of society as a whole, and increased jadedness toward the medical profession overall (10). Idealism decline begins earlier than noted in other studies, implying a need for curricular interventions in the first two years of medical school (10).…”
Section: Discussionmentioning
confidence: 98%
“…This loss of idealism includes a decreased interest in working in underserved communities, feeling of less responsibility for the health of society as a whole, and increased jadedness toward the medical profession overall (10). Idealism decline begins earlier than noted in other studies, implying a need for curricular interventions in the first two years of medical school (10). Supercamp is one of those interventions that make early clinical exposure to the first-year undergraduate program.…”
Section: Discussionmentioning
confidence: 99%